Exploring emotion regulation as a mediator of the relationship between resilience and distress in cancer. Issue 7 (6th June 2019) - Vaughan, Emma; Koczwara, Bogda; Kemp, Emma; Freytag, Corinna; Tan, Wilson; Beatty, Lisa
Abstract: Objectives: Distress in patients with cancer is a significant problem that affects up to 32% of patients. Yet research indicates that 35% of cancer patients do maintain high levels of well‐being. Resilience is one psychological factor implicated as being protective against distress; however, the mechanisms for this relationship are currently unknown. The present study aimed to explore emotion regulation as a potential mediator of the relationship between resilience and distress. Methods: A cross‐sectional survey examining emotional regulation, resilience, and distress was completed by 227 patients from two hospitals with heterogeneous cancer types. Measures included the Difficulties in Emotion Regulation Scale (DERS), the Connor Davidson Resilience Scale, and the Depression, Anxiety, Stress Scale. Results: Difficulties in emotion regulation and resilience explained 33.2% of the variance in distress. Resilience had a significant direct effect on distress, accounting for 15.8% of the variance. However, this effect was no longer significant when difficulties in emotion regulation were controlled for. The indirect effect through difficulties in emotion regulation was significant, b  = 0.009, 95% CI [−0.013, −0.007], suggesting that the effect of resilience on distress was fully mediated by emotion regulation. Parallel mediation analyses also examined the differential effects of the six DERS subscales on the relationship between resilience and distress. Conclusion: These findings suggest that emotion regulation is an important mediator of resilience in cancer. Hence, in patients with cancer, difficulties in emotion regulation (and the DERS specifically) might be a useful focus for screening for patients at risk of distress.